(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Toxic, non-biodegradable heavy metal contaminants found in industrial effluents have beenshown to accumulate in humans and other animals via the food chain. Natural geological weathering,processing of ores, usage of metals, landfill trash, livestock, animal and human excrements, urban run-off,and re-use of drainage water and sewage effluents all contribute to the issue, which is most common inplaces with high concentrations of industry. Heavy metals also infiltrate water via agricultural usage ofmetal coating, insecticides, fertilizers, etc. Industrial effluents include heavy metal ions like cadmium(II)and chromium(VI), which are hazardous and non-biodegradable and may accumulate in humans via thefood chain. Pseudo-first and second order models were used. Different kinetic models have beendeveloped to analyze experimental data in order to learn more about the factors that influence the rate ofadsorption of cadmium (II) and chromium (VI) ions onto various adsorbents.